PENGARUH PERENDAMAN AIR PDAM BANDARMASIH TERHADAP KEKASARAN PERMUKAAN GIGI PASCA PENGAPLIKASIAN KARBAMID PEROKSIDA 20% - Muhammad Nabiel Taqiyuddin Ham; Agung Satria Wardhana; Muhammad Yanuar Ichrom Nahzi; Isnur Hatta; Dewi Puspitasari (Dentin, 2024)
Background: One of the treatments to overcome the problem of discolored teeth is to do tooth whitening or bleaching. The tooth whitening agent that is often used is carbamide peroxide which is applied directly to the tooth enamel surface. Several factors that can affect tooth enamel are the degree of acidity or potential hydrogen (pH), acid concentration, dissolving time and the presence of calcium-like ions, and the level of water hardness. Most of the people in Banjarmasin City still frequently use PDAM water as drinking water and for daily use Objective: To analyze the effect of immersing PDAM water and distilled water on tooth surface roughness after application of 20% carbamide peroxide. Methods: Using a pure experimental design with the Posttest Only With Control Group Design and simple random sampling technique. The total sample was 16 maxillary first premolars which were divided into 3 treatment groups and 1 control group. Results: analysis of the One Way Anova test with Bonferroni's Post-Hoc showed no difference in roughness between the PDAM water immersion and distilled water groups with or without the application of 20% carbamide peroxide (p>0.05). There was a difference in roughness between the group that was given carbamide peroxide and the group that was not given carbamide peroxide 20% (p<0.05). Conclusion: There is an effect of PDAM water immersion on tooth surface roughness after application of 20% carbamide peroxide, but the resulting roughness is not significant.Keywords: PDAM water, Tooth Surface Roughness, 20% Carbamide Peroxide